Effectiveness Of Indonesian Sharia Banks With Islamic Values Using Data Analysis Envelopment Method - Roikhan Mochamad Aziz; Intan Agustin Wulandari; Annisa Nur Qaidah; Pandu Priantoro; Syafnavebiola Syafnavebiola (JURNAL ONLINE INSAN AKUNTAN, 2023)
This study discusses the relationship between the effectiveness of company performance and the value of worship in the company with the benchmark used is Return on Assets and several variables related to prayer. In this case, the authors make samples are Indonesian Islamic Commercial Banks. The purpose of this study is to discuss the relationship between the value of worship with increasing company performance. The research analysis uses the Research Data Envelopment Analysis methodology and the Islamic values of Indonesian Islamic Banks. The data used is the financial statements of Indonesian Islamic Commercial Banks with two input and output variables. This method is basically a linear programming technique based on nonparametric approach, which works by identifying entities whose inputs and outputs have not been evaluated. The level of reflexivity shows that the congregational prayer conditions for Bank Syariah Indonesia employees are going well. This can be seen based on the reflexivity score in 2019 of 72.2%, then decreased in 2020 to 60%. This is due to the Covid-19 outbreak that hit Indonesia in early 2020. Then in 2021, the value of worship in this company again rose to 76.5% in line with normal conditions after the covid pandemic that hit in 2020. The value of prayer tends to has a big effect on increasing the effectiveness of the company's performance Seen from the input variable at Bank Syariah Indonesia.